Growth Monitoring of Infants in an urban area of Sri Lanka – a Clinical Audit - Sithamparapillai, K.; Samaranayake, D.; Wickramasinghe, P. (Postgraduate Institute of Medicine University of Colombo, 2024)
Background and objective Regular monitoring of growth in children is important to detect abnormal growth and implement timely interventions. The aim of this audit was to assess the level of adherence to the national guidelines on growth monitoring during infancy in children attending the immunization clinic of a tertiary care hospital Methods A clinical audit was conducted in 141 children aged 12 and 18 months attending an immunization clinic at the Lady Ridgeway Hospital, Colombo, Sri Lanka. Data on growth assessment were extracted from the Child Health Development Record. The Sri Lanka national guidelines for growth monitoring recommend that weight should be monitored monthly and length should be checked at 4 and 9 months during infancy. More frequent monitoring is recommended if there are any concerns regarding growth. Results Data of 141 children were available for analysis. There were 41.8% (n=59) girls and 77.3% (n=109) were 18 months old. Weight-for-age was <-2SD in 18.4% (n=26), length-for-age <-2SD in 12.1% (n=17) and weight-for-length <-2SD in 15.6% (n=22). Birth weight was recorded in all while length and OFC at birth were recorded in 93.6% (n=132) and 97.9% (n=138) respectively. There were ≥ 9 weight measurements plotted during infancy in 75.9% (n=107). Length was plotted only in 56% (n=79) at 4 months of age, although 92.9% (n=131) had attended the clinic. But length was plotted at least once between 1-6 months in 83% (n=117). Length was not plotted at 9 months in 55.3% (n=78). Of them, 73.1% (n=57) had attended the clinic at 9 months. Length was not measured between 6-12 months in 29.8% (n=42). Frequency of weight and length measurements were significantly lower between 7-12 months of age compared to 1-6 months of age (weight; p<0.001 and length; p=0.02). Weight faltering was noted at some point during infancy in 60.3% (n=85) and 78.8% (n=67) of them had at least one weight-for-length plotted while 28.2% (n=24) of them had two or more recordings plotted. Conclusion There is a need to strengthen growth monitoring during infancy in this population with a high prevalence of growth faltering.
Keywords: Growth monitoring; Infants; Growth indices